2021
DOI: 10.1108/acmm-03-2020-2270
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of pre-oxidation time for corrosion resistance of cobalt based coating alloy in mixed sulphates

Abstract: Purpose This study aims to optimise the effect of pre-oxidation on hot corrosion behaviour of Tribaloy T-900 at 900 °C in mixed Na2SO4 and K2SO4. Design/methodology/approach Prior to hot corrosion experiment, pre-oxidation treatments were carried in ambient air at 900 °C for 1, 5 and 10 h, respectively. The hot corrosion experiments were performed in a box type furnace at 900 °C. Both surfaces of specimens were brushed with saturated salt solution of 75 wt.% Na2SO4 + 25 wt.% K2SO4. After brushing, the salt-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The failure mechanism of the coating system has been studied and explained by a large number of scholars (Li et al, 2023;Rehman et al, 2021). Some researchers have found that the failure process of the coating/metal system consists of three steps: (1) the coating system is in the corrosive medium and good isolation protects the metal substrate from corrosion; (2) the external corrosive medium penetrates from the microscopic defects of the coating, constantly reducing the protective effect of the coating; and (3) when the corrosive medium reaches the metal substrate, the metal corrosion occurs under the coating, which caused the metal and the coating stripping off.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure mechanism of the coating system has been studied and explained by a large number of scholars (Li et al, 2023;Rehman et al, 2021). Some researchers have found that the failure process of the coating/metal system consists of three steps: (1) the coating system is in the corrosive medium and good isolation protects the metal substrate from corrosion; (2) the external corrosive medium penetrates from the microscopic defects of the coating, constantly reducing the protective effect of the coating; and (3) when the corrosive medium reaches the metal substrate, the metal corrosion occurs under the coating, which caused the metal and the coating stripping off.…”
Section: Introductionmentioning
confidence: 99%
“…The failure mechanism of the coating system has been studied and explained by a large number of scholars (Li et al. , 2023; Rehman et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%